94.0k views
5 votes
If f(x) = x2 + 7x and g(x) = 3x - 1, what is f(g(x))?

1 Answer

5 votes

Answer:

f(g(x)) = 9x^2 + 15x - 6

Explanation:

We are using function g(x) = 3x - 1 as the input to function f(x) = x^2 + 7x.

Starting with f(x) = x^2 + 7x, substitute g(x) for x on the left side and likewise substitute x^2 + 7x for each x on the right side. We obtain:

f(g(x)) = (3x - 1)^2 + 7(3x - 1).

If we multiply this out, we get:

f(g(x)) = 9x^2 - 6x + 1 + 21x - 7, or

f(g(x)) = 9x^2 + 15x - 6

User DeepakPanwar
by
5.2k points